Genesis of carbonate minerals in shale of Qingshankou Formation, Sanzhao Sag, Songliao Basin - Xia WU; Ruiqian CHEN; Xin BAI (Shiyou shiyan dizhi)
To reveal the significance of carbonate minerals in continental shale for shale oil and gas exploration and development, this paper takes the carbonate mineral developed shale from the Qingshankou Formation in the Sanzhao Sag of the Songliao Basin as the research object. Through thin-section observation, X-ray diffraction (XRD), carbon and oxygen isotope analysis, and major and trace element analysis, the types and development characteristics of carbonate minerals were analyzed in depth. The material sources and genetic mechanisms for carbonate mineral formation were discussed, and how carbonate mineral development affected shale oil and gas enrichment was explained in detail. The study revealed that the shale from the Qingshankou Formation in the Sanzhao Sag developed three types of calcite (biogenic shell carbonates, micritic calcite, and sparry calcite) and two types of dolomite (micritic and fine-grained dolomite). Through the analysis of stable carbon and oxygen isotopes, and major and trace elements, it was shown that the carbonates in the study area mainly formed in a stratified, anoxic, reducing, and moderately to highly productive environment within a closed saline lake. The genesis of different types of carbonate minerals varied. Biogenic shell carbonates, micritic calcite, and micritic dolomite were mainly controlled by biochemical action, and the sparry calcite and fine-grained dolomite were formed through recrystallization. Results from rock organic carbon content and rock pyrolysis tests indicated a positive correlation between carbonate content and total organic carbon (TOC) content and a positive correlation between TOC content and hydrocarban generation potential(S1+S2)values, indicating that the carbonate mineral developed intervals in continental shale were high-quality shale development zones. Additionally, the formation of intercrystalline and dissolution pores associated with carbonate minerals created storage conditions for the accumulation of oil and gas in the shale.